1992
DOI: 10.1164/ajrccm/146.4.888
|View full text |Cite
|
Sign up to set email alerts
|

A Community-based Study of the Epidemiology of Asthma: Incidence Rates, 1964–1983

Abstract: To determine whether the incidence of asthma had increased in Rochester, Minnesota, from January 1, 1964 through December 31, 1983, we used a population-based computer-linked medical diagnosis system to identify individual medical records with diagnosis of asthma or other conditions mimicking asthma. All records were reviewed using explicit predetermined diagnostic criteria; we identified 3,622 incident cases of asthma, including definite asthma (n = 1,547), probable asthma (n = 952), and single wheezing episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
387
3
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 657 publications
(424 citation statements)
references
References 11 publications
18
387
3
10
Order By: Relevance
“…Although there exist sex-based differences in the natural history of both diseases, we did not see consistent enrichment of the gene sets associated with sex in the developing lung (G1 and G3) for these disease genes. Our results suggest that sex-specific effects previously described in the third trimester (29) are not observed during earlier phases of gestation. Finally, it is possible that these transcriptomic changes are due to a more dominant effect of postconception age when compared with sex differences in the first two trimesters.…”
Section: Discussionsupporting
confidence: 51%
“…Although there exist sex-based differences in the natural history of both diseases, we did not see consistent enrichment of the gene sets associated with sex in the developing lung (G1 and G3) for these disease genes. Our results suggest that sex-specific effects previously described in the third trimester (29) are not observed during earlier phases of gestation. Finally, it is possible that these transcriptomic changes are due to a more dominant effect of postconception age when compared with sex differences in the first two trimesters.…”
Section: Discussionsupporting
confidence: 51%
“…Often physicians diagnose asthma at an older age and retrospectively attribute the onset of asthma to a specific year. In the PSPN study the incidence rate in the age group 1-14 years was 3.74 cases per 1000 per year, considerably higher than the 1.4 cases/1000/year found by Yunginger et al in 1992. 20 The PSPN study observed a higher incidence rate in the age group 0 -4 years (5.93 cases/1000/year).…”
Section: Comparison Of Findings With Other Published Studiesmentioning
confidence: 76%
“…In the PSPN study the incidence rate in the age group 1-14 years was 3.74 cases per 1000 per year, considerably higher than the 1.4 cases/1000/year found by Yunginger et al in 1992. 20 The PSPN study observed a higher incidence rate in the age group 0 -4 years (5.93 cases/1000/year). It is possible that some of the children diagnosed with asthma were suffering from recurrent wheezing or bronchiolitis.…”
Section: Comparison Of Findings With Other Published Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…Allergic asthma usually starts early in life (8,9) and most asthmatic children are allergic. The early occurrence of allergic asthma suggests that prenatal influences are of importance (10,11) and it is likely that defects in early development of the lung, as well as the immune system are involved in the pathogenesis of asthma.…”
mentioning
confidence: 99%